Water Quality Prediction Using Data Mining techniques: A Survey (International Journal of Engineering and Computer Science, 2017)
Data Mining is the set of activities used to find new, hidden, or unexpected patterns in data. Many organizations are now using these data mining techniques. Research in data mining continues growing in business and in learning organization over coming decades. Data mining methods may be classified by the function they perform or by their class of applications. Using this approach, four major categories of processing algorithms and rule approaches emerge: 1) Classification, 2) Association, 3) Sequence and 4) Cluster. This paper explores various data mining techniques like Artificial Neural Network, Back propagation, MLP, GRNN, Decision Tree etc. used in prediction of water quality. This survey focuses on how data mining techniques are used for water quality Prediction is analyzed